Improving mechanical properties of PVA based nano composite using aligned single-wall carbon nanotubes. (11th September 2019) - Luan, X; Younse, H; Hong, H; Peterson, G P
Abstract: The fabrication and characterization of PVA films reinforced with single-wall carbon nanotubes (SWNTs) and Fe2 O3 nanoparticles were investigated. The composite made with sodium dodecylbenzene sulfonate (NaDDBS) dispersed SWNTs at a 4 wt% loading percentage demonstrated good dispersion and resulted in the highest tensile strength (97 MPa) of all the SWNT reinforced films tested, and a 21% increase compared to the neat PVA film (80 MPa). The study revealed that with 10 wt% of NaDDBS, only 10–20 min of sonication was necessary to obtain uniform and stable SWNT dispersion in water. Moreover, applying a magnetic field (H = 0.12 kG) to the composite film to align the SWNTs resulted in a tensile strength of 106.4 MPa. Using 5 wt% of Fe2 O3 the tensile strength increased to 115 MPa after exposing the composite film to the magnetic field for 60 min during the drying process to align the carbon nanotubes. In addition, the tensile property of the composites was enhanced by annealing the polymer composites in a vacuum oven at 75 °C for 2 h.